2009
DOI: 10.1208/s12249-009-9346-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclodextrin Complexation on the Aqueous Solubility and Solubility/Dose Ratio of Praziquantel

Abstract: Abstract. Praziquantel (PZQ), the primary drug of choice in the treatment of schistosomiasis, is a highly lipophilic drug that possesses high permeability and low aqueous solubility and is, therefore, classified as a Class II drug according to the Biopharmaceutics Classification System (BCS). In this work, β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD) were used in order to determine whether increasing the aqueous solubility of a drug by complexation with CDs, a BCS-Class II compound like PZQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…1). These findings confirmed previous results of Arrua et al (Arrua et al, 2015) and Maragos et al (Maragos et al, 2009).…”
Section: Comparative Phase Solubility Study With Maltodextrin and Cycsupporting
confidence: 93%
See 1 more Smart Citation
“…1). These findings confirmed previous results of Arrua et al (Arrua et al, 2015) and Maragos et al (Maragos et al, 2009).…”
Section: Comparative Phase Solubility Study With Maltodextrin and Cycsupporting
confidence: 93%
“…A linear profile of the solubility increase of CDs indicated a stoichiometry of 1:1, a positive or negative deviation from linearity would be associated with a higher order interaction or a self-association of CDs (Loftsson et al, 2005). Whereas this conclusion is in line with Maragos et al (Maragos et al, 2009), de Jesus et al (de Jesus et al, 2006) and El-Arini et al (El-Arini and Leuenberger, 1996), other studies reported a stoichiometry of 1:2 (Arrua et al, 2015).…”
Section: Comparative Phase Solubility Study With Maltodextrin and Cycsupporting
confidence: 52%
“…The interaction between PZQ and other excipients was also studied in order to improve the low solubility of the drug, for example, with calcium carbonate [ 18 , 19 , 20 ], β-cyclodextrins [ 21 , 22 , 23 ], polyvinyl-pyrrolidone [ 24 , 25 ], polyethylene glycols [ 26 , 27 , 28 ], sodium starch glycolate [ 29 ], phosphatidylcholine–containing liposomes [ 30 ], layered double hydroxides [ 31 ], among others. Specifically, the interaction between PZQ and montmorillonite in aqueous medium was previously studied, although no improvements of in vitro dissolution and absorption rates were observed [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it suggested that the effect of non-inclusion complexation in the solubilization ability of HP-␤-CD was more evident than that of ␤-CD, resulting in the better solubilization ability of the former. It should be also taken into account that the low solubility of ␤-CD was attributed to the strong inter-and intra-molecular hydrogen bond formation between the secondary hydroxyl groups of CD molecules, while no such bonding was observed in the case of HP-␤-CD due to partial substitution of the secondary hydroxyl groups of the CD molecule with hydroxypropyl groups (Maragos et al, 2009). Similar to HP-␤-CD, the methyl groups of Me-␤-CD disrupted intra-molecular hydrogen bonding, but also enlarged the whole cavity of the molecule by extending the secondary hydroxyl side and narrowing the primary hydroxyl side of the cone.…”
Section: Comparison Of Various Cdsmentioning
confidence: 99%